2007
DOI: 10.1638/2006-0065.1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Subpalpebral Lavage Systems Used for Llamas (Lama Glama) and a Harbor Seal (Phoca Vitulina)

Abstract: Subpalpebral lavage systems (SPLSs) were adapted for use in zoo llamas (Lama glama) and a wild harbor seal (Phoca vitulina) during therapy for severe ulcerative keratitis or corneal perforation. One llama presented with a melting corneal ulcer caused by Pseudomonas aeruginosa, which necessitated frequent application of a topical ophthalmic antibiotic. The lavage system was used routinely during the day and was connected to a balloon infusion system at night to allow for continuous medication administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Subpalpebral lavage placement was performed exclusively in the ventromedial eyelid in this study, but ventrolateral and dorsal placement has been reported for dogs, 19 horses, 14,15 a llama, a harbor seal 17 and humans 16 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Subpalpebral lavage placement was performed exclusively in the ventromedial eyelid in this study, but ventrolateral and dorsal placement has been reported for dogs, 19 horses, 14,15 a llama, a harbor seal 17 and humans 16 …”
Section: Discussionmentioning
confidence: 95%
“…Owners can be trained to operate the SPL system allowing the patient to be managed at home. SPL use has been reported in humans, 16 llamas, and a harbor seal 17 . A single report 18 and a case series of four dogs 19 describe SPL use for management of corneal ulceration in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…P aeruginosa was cultured from all cases of melting ulcers that developed during rehabilitation and this pathogen has been well described in such pathology in other species too (Miller and others 1994, Whitley 2000, Keller and Hendrix 2005, Borkowski and others 2007). Pseudomonas has been isolated from small numbers of ocular swabs from pinnipeds with inflamed eyes before, although the exact nature of the pathology is unclear (Johnson and others 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As well as topical antibiotic therapy, there are other medical and surgical treatment modalities that may be appropriate in cases of melting ulcers, for example, autologous serum administration, subpalpebral lavage systems, subconjunctival injections of antibiotics, systemic antibiosis and surgery (Crispin 2002, Borkowski and others 2007, Ledbetter and Gilger 2013). However, these are beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Subpalpebral lavage systems may be warranted in camelids that require frequent treatment or in those that become refractory to direct application. 134 Topical antibiotics may be given more frequently (up to 6 times a day), a fluoroquinolone antibiotic may be selected for better corneal penetration, or a combination of both may be tried. 126 Serum may be collected from the patient to be administered The central cornea has a lackluster appearance with a central ring of white cellular infiltrate with characteristic "satellite" lesions and perilesional corneal edema.…”
Section: Normal Ocular Anatomymentioning
confidence: 99%